Optimal configuration of electronic networking technologies for supporting D/B projects - Abduh, Muhamad; Skibniewski, Miroslaw J. (Journal of Civil Engineering and Management, 2002)
Electronic Networking Technologies (ENT) have only begun to make inroads into the construction industry practice. ENT provide unparalleled opportunities for the construction industry to introduce new and innovative way of processing information. These opportunities also present a number of challenges in terms of how to plan for and implement ENT services. There is a significant potential for large benefits from the correctly developed and applied ENT solutions for construction projects activities. This paper presents an assessment model for determining utility of various ENT services and the optimal configuration of ENT services for D/B projects. Web and FTP services were included in the ENT configuration as the tools to support all activities that require information retrieval. E-mail, list server, video conferencing, and remote access services were included in the ENT configuration as communication tools. An implementation scenario of the utility assessment model and a discussion on issues that should be considered in implementing ENT services in construction are presented. Frist Published Online: 30 Jul 2012